To solve the equation \( 2x - 5 = 3(4x + 5) \), here are the steps simplified:
Step 1: Distribute on the right side:
\( 3(4x + 5) \) becomes \( 12x + 15 \).
So the equation is now \( 2x - 5 = 12x + 15 \).
Step 2: Move all \( x \) terms to one side.
Subtract \( 2x \) from both sides:
\( -5 = 10x + 15 \).
Step 3: Move the constant to the other side.
Add 5 to both sides:
\( 0 = 10x + 20 \).
Step 4: Isolate \( x \).
Subtract 20 from both sides, then divide by 10:
\( -20 = 10x \) → \( x = -2 \).
So the four steps are:
- Distribute.
- Move \( x \) terms to one side.
- Move constants to the other side.
- Isolate \( x \).